2010
DOI: 10.1002/ange.201002090
|View full text |Cite
|
Sign up to set email alerts
|

Eintopfsynthese von Menthol in Gegenwart eines hoch diastereoselektiven Au/MgF2‐Katalysators

Abstract: Ohne hochtoxische Verbindungen wie KCN und eine thermische Nachbehandlung wurden Au/MgF2‐Komplexe durch eine einfache simultane Nassimprägnierung mit Tetrachlorogoldsäure als Goldvorstufe zugänglich. Einer der so erhaltenen Komplexe weist einzigartige katalytische Eigenschaften auf und ermöglichte die heterogen katalysierte hoch diastereoselektive Eintopfreaktion von Citronellal zu (±)‐Menthol (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Therefore, with the aim of a one‐pot hydroacetylation alternative in mind we have focused on a bifunctional catalyst (i.e., one exhibiting both hydrogenation and acidic functions). Taking into account that the nanoscopic acidic hydroxylated metal fluorides proved to be highly efficient for the acetylation of menadiol to MDD, we prepared a series of bifunctional Au 3+ /MgF 2 (or AlF 3 ) catalysts using an easy and facile incipient wetness impregnation method following a reported procedure 16. Materials with 1 wt% and 4 wt% Au were obtained in this way.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, with the aim of a one‐pot hydroacetylation alternative in mind we have focused on a bifunctional catalyst (i.e., one exhibiting both hydrogenation and acidic functions). Taking into account that the nanoscopic acidic hydroxylated metal fluorides proved to be highly efficient for the acetylation of menadiol to MDD, we prepared a series of bifunctional Au 3+ /MgF 2 (or AlF 3 ) catalysts using an easy and facile incipient wetness impregnation method following a reported procedure 16. Materials with 1 wt% and 4 wt% Au were obtained in this way.…”
Section: Methodsmentioning
confidence: 99%
“…The gold hydroxide 2 [22] was treated with LiHBEt 3 in toluene at À78 8C and subsequent stirring of the reaction mixture at room temperature for 15 min provided 3 as a dark yellow crystalline complex in 75 % yield. The structural assignment was confirmed by an X-ray crystal structure analysis (AuÀH 1.616 (16) ; the hydride was located in a difference density map and refined; bond length to the trans ligand: Au À N 2.035 (3) ).…”
mentioning
confidence: 77%
“…This finding supported mechanisms that propose the active participation of gold(I) hydrides in the dehydrogenative silylation of alcohols [10,11] [the hydrolysis of IPrAuH [8] (IPr = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene) would nicely fit into that picture], the formation of hexabutyldistannane by intermolecular dehydrogenative dimerization, [12] the hydrosilylation of ketones and imines, [11,13] the hydroboration of imines, [14] C À H activation, [15] and the enantioselective hydrogenation of alkenes and imines. [16] And it also could explain reactions for which the intermediacy of gold hydrides could be assumed, like the first reported homogeneous gold-catalyzed hydrogenation [17] and the goldcatalyzed synthesis of pyridines, in which the final step is the dehydrogenation of the initially formed dihydropyridine intermediate. [18] Corma et al have suggested gold(III) monohydrides as intermediates in homogeneous gold-catalyzed hydrogenation reactions, a pathway supported by DFT calculations.…”
mentioning
confidence: 99%
“…B. heterogene Goldkatalysatoren für selektive Hydrierungen eingesetzt, [5] und für Gold-Hydrierungskatalysatoren auf Zirconiumoxidträgern wurden Au 3+ -Ionen als aktive Zentren vorgeschlagen. [6] Gold(I)-und Gold(III)-Hydride wurden als Zwischenstufen zahlreicher homogenkatalysierter Prozesse postuliert, wie Hydrierungen, [7,8] Hydrosilylierungen, [9] dehydrierende Alkohol-Silylierungen, [10] Hydroborierungen [11] und andere organische Reaktionen. [12] Corma und Mitarbeiter verwendeten immobilisierte Gold-(III)-Chelatkomplexe als Hydrierungskatalysatoren und untersuchten die Rolle von Gold(III)-Hydriden detailliert mit kinetischen Methoden und Modellrechnungen.…”
unclassified